Aspinwall area, general view of a private residence, Brookline, Massachusetts, 6 of 8. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
Exterior view of a residence in the Aspinwall area in Brookline. Slide 6 of 8.; Caption on image: Aspinwall Area (2) Gen. view of area.; Binder Number 4. Pocket Number: 15.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.